An environmentally aceptable primer for galvanized steel: Formulation and evaluation by SVET - Simões, A. M. P. (2011)
The object of this paper was to formulate a two-pack wash primer employing aluminium phosphosilicate as active anticorrosive pigment instead of basic zinc chromate. The anticorrosive action of the primer was evaluated by the polarization technique and the scanning vibrating electrode technique (SVET). The exposed surface was then examined by scanning electron microscopy (SEM) and the surface composition determined by energy dispersive X-ray (EDX) analysis. The primer was finally integrated in a complete paint scheme whose anticorrosive performance was evaluated by the salt spray chamber and electrochemical impedance spectroscopy. The adhesion of the primer plus a painting system was also evaluated by standard ASTM D 3359-90 test method. The wash primer pigmented with zinc chromate was used as reference. Results indicated that basic zinc chromate could be replaced by the more eco-friendly washprimer containing aluminium phosphosilicate.